Implementation of the Problem Based Learning Model on Student Learning Outcomes at SD Negeri Neuheun on the Material of Belief in Allah and Rasullullah - Elnawati; Yunarlisa (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
This study aims to determine the effectiveness of the application of the Scientific Learning approach to the learning outcomes of grade IV students of SD Negeri Neuheun on the material of Faith in Allah and His Messenger. The background of this research is the low understanding of students of Islamic Religious Education (PAI) material which has an impact on low learning outcomes under the Minimum Completeness Criteria (KKM). This research uses the Classroom Action Research (PTK) method which is carried out in two cycles, with each cycle including the stages of planning, implementation of actions, observation, and reflection. The research subjects amounted to 20 fourth grade students of SD Negeri Neuheun. The results of the study show that the application of the Scientific Learning approach which includes the steps of observing, questioning, reasoning, trying, and communicating is able to significantly increase student activeness and learning outcomes. Students become more enthusiastic, actively participate in the learning process, and are able to understand the concept of faith in Allah and His Messenger more deeply. The increase in learning outcomes is also shown by the increase in the number of students who achieve grades above the KKM after the implementation of the action. Thus, the Scientific Learning approach has proven to be effective in improving learning outcomes and the quality of PAI learning in elementary schools.